Supramolecular chiral inversion and regulation of phenylalanine-based organogels in low-polarity achiral solvents - Zhang, Wannian; Yu, Fang; He, Yu-Peng (Communications chemistry, 2025)
Metamaterials with supramolecular chirality have been widely developed in many fields, and their assembly modes provide valuable insights for understanding living systems. In this work, we achieved for the first time the inversion of supramolecular chirality in organogels using a low-polarity achiral solvent. Furthermore, the regulation of supramolecular chirality was achieved through structural modification of the achiral moieties. Additionally, the impact of hydrogen bond variability on the modulation of supramolecular chirality was investigated by replacing the O atom with the N atom. Subsequently, the mechanisms governing supramolecular chirality modulation through low-polarity solvents and weakly polar structural motifs was elucidated. The results demonstrate that weak-polarity solvents, achiral long-chain moieties, and hydrogen bonds can individually serve as effective modulators for regulating intermolecular assembly patterns, thereby exerting critical influence on the emergence of supramolecular chirality. These findings establish a robust foundation for the precise construction and manipulation of supramolecular chirality in organogel systems. Methods for regulating supramolecular chirality in gels rely on varying the chiral factor of the gelator or increasing the solvent polarity. Here, the authors demonstrate the use of a low-polarity achiral solvent to achieve supramolecular chirality inversion in organogels and show that weak-polarity solvents, achiral long-chain moieties, and hydrogen bonding interactions can effectively modulate intermolecular assembly patterns.